EDITORIAL - Lima Jr., L. F. de; Gimenes, Marcelino Luiz; Aznar, Martin; Scheer, A. de Paula (Revista de Engenharia Térmica, 2005)
This special issue of Engenharia Térmica presents selected papers from the XV Brazilian Congress of Chemical Engineering (COBEQ) and II Brazilian Congress of Phase Equilibrium that took place in Curitiba, Paraná State between 26 and 29 September 2004. The XVth edition of COBEQ almost completes three decades of the Congress existence. Since 1975 it is the most important event in the area, not only because of its extensive coverage, but also because it is a great opportunity to the Chemical Engineering community to exchange ideas and update the scientific information in different areas. The Congress main theme was the relationship between Chemical Engineering and sustainable development. There were 798 papers presented in the Congress. They were distributed in eight areas, which included: Environment and Clean Technology; Biotechnology and Food; New Materials Products and Technologies; Chemical Reactor and Catalysis; Transport Phenomena and Particulated Systems; Separation Engineering and Thermodynamics. The implementation of the event was under the responsibility of the Brazilian Association of Chemical Engineering (ABEQ) and the organization of the current edition was under the responsibility of the Chemical Engineering Departments of Federal University of Paraná (UFPR) and State University of Maringá (UEM). The organizing committee would like to thank the scientific committee composed by researchers from several institutions for their contributions, and to the funding agencies and the industries for the support provided by them. We hope that this Engenharia Térmica special issue, together with the Conference Proceedings will be a valuable reference document to the scientific and industrial community and that will contribute to the engineering progress.